The role of teamwork in nursing - Prevyzi, Evangelia (Health & Research Journal, 2017)
Introduction: Patients’ health and safety depends on the application of complex treatments and advanced therapeutic technologies and the creation of team work. Aim: The aim of the present literature review was to determine the role of the team work on nursing. Methodology: This systematic review was based in the research of publised systematic reviews and research studies which were drawn from foreign electronic databases (Pubmed, Medline, Scopus) and Greek (Iatrotek), on the role of the working group on nursing and were carried out during the period 2006-2017. 32 studies were found that met the criteria for their participation in the review. Results: The promotion of team work is essential for the high level of quality in healthcare services. Achieve the proper functioning of nursing departments as changing nurses’ working conditions. The team work, makes changes to the way nurses action both within the team structure, goal setting powers and the monitoring thereof, evaluation of group attitudes, mutual support and communication between team members. Conclusions: The promotion of the culture of the team work on nursing is crucial. The update of the nursing staff knowledge needs to focus more on the effectiveness of team work. The upgrading of nursing practice requires adequate knowledge and excellent communication and collaboration among nurses